ChemInform Abstract: Calcining Temperatures of Sr1‐3xEuxDy2xAl2O4 (x = 0—0.12) Phosphors Prepared Using the Potassium Carbonate Coprecipitation Method - Liang, Chen‐Jui; Siao, Hao‐Yi (ChemInform, 2016)
The title phosphors are prepared by the potassium carbonate coprecipitation method followed by calcination.